CCL2 mediates the circadian response to low dose endotoxin - Duhart, José Manuel (2016)
The mammalian circadian system is mainly originated in a master oscillator located in the suprachiasmatic nuclei (SCN) in the hypothalamus. Previous reports from our and other groups have shown that the SCN are sensitive to systemic immune activation during the early night, through a mechanism that relies on the action of proinflammatory factors within this structure. Chemokine (C-C motif) ligand 2 (CCL2) is induced in the brain upon peripheral immune activation, and it has been shown to modulate neuronal physiology. In the present work we tested whether CCL2 might be involved in the response of the circadian clock to peripheral endotoxin administration. The CCL2 receptor, C-C chemokine receptor type 2 (CCR2), was detected in the SCN of mice, with higher levels of expression during the early night, when the clock is sensitive to immune activation. Ccl2 was induced in the SCN upon intraperitoneal lipopolysaccharide (LPS) administration. Furthermore, mice receiving an intracerebroventricular (Icv) administration of a CCL2 synthesis inhibitor (Bindarit), showed a reduction LPS-induced circadian phase changes and Icv delivery of CCL2 led to phase delays in the circadian clock. In addition, we tested the possibility that CCL2 might also be involved in the photic regulation of the clock. Icv administration of Bindarit did not modify the effects of light pulses on the circadian clock. In summary, we found that CCL2, acting at the SCN level is important for the circadian effects of immune activation.